Compact Beam Switching Antenna System for Health Monitoring Doppler Radar at 5.8GHz - Rabbani, Muhammad Aaqib; Abbasi, Haseeb Ur Rahman; Rabbani, Muhammad Saqib (2021 1st International Conference on Microwave, Antennas & Circuits (ICMAC), 2021)
A 2-element beam-steering microstrip antenna array (MAA) system is presented at 5.8 GHz for remote wireless health monitoring (RWHM) in a dynamic environment operating on Doppler radar (DR) principle. A novel compact phase shifting transmission line (TL) mechanism is designed using PIN diode based switching technique. A single delay TL (D-TL) segment is employed in the feeding network to introduce three phase delay stages to steer the antenna beam at 0°and ±26°. The MAA exhibits sufficient gain (>9dBi) and half power beamwidth (HPBW) (47°) to carry out a subject focused vital sign detection from a short distance (<3 m) and 100ͦ angular space.